The Influence of Product Quality on Customer Satisfaction in Conventional Clothing Markets: A Case Study of Economic Geography in Bedoro Village, Sambungmacan - Fitria , Aifina; Rohsulina, Pranichayudha; Bayu (Journal of Geography Science and Education, 2025)
In the current era of globalization, development and competition in the business world are increasingly fierce. One business that has very tight competition is the convection business. A convection business is a business that produces clothing in large quantities, according to consumer demand. This research aims to find out how product quality influences the KDC Konveksi company. Product quality greatly influences customer satisfaction. The progress of a company is influenced by the presence of quality products. A quality product will make the product useful for someone who buys it and the company will become more famous so that many people will know it. In this way, someone will buy a quality product repeatedly. This research uses a Google Form instrument with a qualitative description method. From this research, the results showed that everyone was satisfied with the results of the convection, so it is hoped that this company can maximize sales from previous sales